Percutaneous Endoscopic Gastrostomy Tube Replacement Unexpected Serious Events. (February 2014) - Triantafyllou, Konstantinos; Papanikolaou, Ioannis S.; Stasinos, Ioannis; Polymeros, Dimitrios; Dimitriadis, George D.
Percutaneous endoscopic gastrostomy tubes are replaced due to clogging, breaking, and dislodgement. There are potential complications associated with these procedures, including intraperitoneal placement of the tube and peritonitis, which can occur even in the presence of a well established stoma site. Herein we present a case series of 3 patients with mature gastrocutaneous tracks, who developed peritonitis following tube replacement. In the absence of a consensus or international guidelines regarding the management of patients requiring percoutaneous endoscopic gastrostomy tube replacement, emphasis should be given on prevention of severe adverse events and on early anticipation of their occurrence. Clinical experience indicates that recognition of high-risk procedures, selection of the appropriate replacement method and confirmation of correct tube placement can improve patients' safety and reduce the complications rate.